Maracas Beach Fishing Area, Trinidad - Otto, E.E. (Ace Printery, Trinidad, 2009)
Description on the back of the postcard reads "Fishing Village, Maracas Beach: About half an hour's drive from Port of Spain, Trinidad".
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bays--Trinidad and Tobago; Beaches--Trinidad and Tobago; Fishing villages--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Beachgoers--Trinidad and Tobago; Leisure--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Fishers--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Maracas Bay